COMPARATIVE ANALYSIS OF REPRODUCTIVE AND NESTING BEHAVIOR IN SEVERAL SPECIES OF EURYSTERNUS DALMAN (COLEOPTERA : SCARABAEINA E: EURY STERNINI) - Huerta, Carmen; Halffter, Gonzalo; Halffter, Violeta (Instituto de Ecología, A.C., 2003)
This work aims at achieving a synthesis, and for this reason incorporates much unpublished information (more than 50% of all the data presented here). The goal is a better overall vision of nesting behavior and associated processes of the nine Eurysternus species for which data are available. Thus, we used not only published information, but also information from laboratory notebooks (covering 1967 to 2001) and observations on species never formally studied to date. Eurysternus, a morphologically quite homogeneous genus, shows two distinct types of nesting behavior (i.e., that of E. foedus, which makes brood-masses; and that of other Eurysternus species, so far as they are known, which make brood-balls), representing two directions in the evolution of Scarabaeinae nesting behavior. Beyond this, among the species showing the most common nesting behavior pattern—with several brood-balls integrated in a compound nest—some species care for their young after oviposition (subsocial species) while others do not. A review of data on a total of 307 Eurysternus pairs (representing seven species) maintained and studied in the laboratory, and four Huerta et al.: A nalysis comparative in several species of Eurysternus Eurysternus species (E. deplanatus, E. inflexus, E. jessopi, and E. magnus) whose nests were observed in the field demostrated that some species (though not all) develop two different types of nests (provisional or experimental, and definitive). Infanticide has also been observed, by the mother, by the father, and by both parents (for five of the nine species studied). While much is known in general about Eurysternus nesting behavior, synthesizing the data available raises new questions.